DEVELOPING A CLIMATE-BASED RECREATION MANAGEMENT SYSTEM FOR A MEDITERRANEAN ISLAND - Olya, Hossein G. T.; Alipotna, Habib (Parlar Scientific Publications (P S P), 2015)
Weather and climate have a crucial influence on tourism activities. As a result, tourism is vulnerable to the effects of climate change. One important category of such effects is the change in climatic suitability of tourist destinations. This study proposes a model for landscape management based on climate attractiveness for tourists within the context of the Theory of Ecological Modernization ([EM). The modelling process conforms to Ackoff's wisdom hierarchy, which transforms data into information, knowledge and wisdom. Data were obtained from a meteorological station in Northern Cyprus where the Mediterranean Sea and its favorable climate are key resources for the tourism sector. The monthly Tourism Climate Index (TCI) was used at all stations and was digitized in Geographical Information System (GIS) setting. Spatial analysis was performed using Geostatistical methods, and tourism climate maps were produced for a 12 month period, aiming to identify temporal variations of TCI values on the island. A climate-based Recreation Management System (RMS) is proposed to determine three variables that are both spatial and temporal drivers for tourism activities: climate, environment and social factors. The main application of this process is the mitigation of problems of seasonality, as they always pose a challenge for the managers of different destinations.
Keywords: Climate change; GIS; seasonality; Ecological Modernization Theory; Northern Cyprus